2022
DOI: 10.1038/s41467-022-28485-4
|View full text |Cite
|
Sign up to set email alerts
|

GLI transcriptional repression is inert prior to Hedgehog pathway activation

Abstract: The Hedgehog (HH) pathway regulates a spectrum of developmental processes through the transcriptional mediation of GLI proteins. GLI repressors control tissue patterning by preventing sub-threshold activation of HH target genes, presumably even before HH induction, while lack of GLI repression activates most targets. Despite GLI repression being central to HH regulation, it is unknown when it first becomes established in HH-responsive tissues. Here, we investigate whether GLI3 prevents precocious gene expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 79 publications
2
39
0
Order By: Relevance
“…No activity was detected in the remaining 50%, presumably because recombination occurred prior to Shh expression onset in those embryos. Notably, transient Shh activity is also first detectable in controls at 29 somites (completely absent in all embryos at 28 somites; this study Figures 1C, 3, S1A, and S2;in agreement with Zhu et al, 2008;Lex et al, 2022). Within 2 h, by the 30-somite stage (+1 somite) when Shh activity (Ptch1, Gli1 expression) is detected in 100% of control (Shh +/À ) sibling embryos, Shh activity had ceased in all Shh-CKO embryos (Figures 1C and S1A) and subsequently remained absent.…”
Section: A Transient Shh Pulse Restores Normal Limb Development When ...supporting
confidence: 92%
See 2 more Smart Citations
“…No activity was detected in the remaining 50%, presumably because recombination occurred prior to Shh expression onset in those embryos. Notably, transient Shh activity is also first detectable in controls at 29 somites (completely absent in all embryos at 28 somites; this study Figures 1C, 3, S1A, and S2;in agreement with Zhu et al, 2008;Lex et al, 2022). Within 2 h, by the 30-somite stage (+1 somite) when Shh activity (Ptch1, Gli1 expression) is detected in 100% of control (Shh +/À ) sibling embryos, Shh activity had ceased in all Shh-CKO embryos (Figures 1C and S1A) and subsequently remained absent.…”
Section: A Transient Shh Pulse Restores Normal Limb Development When ...supporting
confidence: 92%
“…We considered the possibility that either persistent low-level, residual pathway activity or a long-range response during the transient Shh expression pulse had escaped detection but think this unlikely for the following reasons. (1) Low-level Shh activity persistence, owing to either incomplete Shh recombination or some compensatory feedback leading to ectopic Hh ligand activation, should result in the continued activation of direct targets Gli1 and Ptch1, which are detectable at much lower levels than is Shh RNA (Lewis et al, 2001;Lex et al, 2022;Zhu et al, 2008). Furthermore, Shh-expressing cells proliferate in the early limb bud to give rise to d4/d5, and activation of direct target reporters should be increasingly apparent over time (E10.5-11.5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study found that the engagement of Hh ligands to Patched can be negatively regulated by endogenous antagonist of Hh ligands, i.e., hedgehog-interacting protein (Hhip). Besides, the translocation of Gli 1 from the cytoplasm to the nucleus is concomitant with the activation of Hh signaling [ 65 , 66 ]. Hh signaling has been shown to be involved in the AOM/DSS-induced CAC, and suppression of Hh signaling contributed to the amelioration of CAC [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A low-level persistence of Shh pathway activation, owing to either incomplete recombination to delete Shh during the period of tamoxifen activity or to some compensatory feedback leading to ectopic Shh activation or activation of another Hh ligand should all result in the continued activation of direct targets Gli1 and Ptch1 , which are detectable at much lower levels than is Shh RNA 5, 12, 42 . Furthermore, because Shh-expressing cells proliferate in the early limb bud (later giving rise to posterior digits), the activation of direct target reporters should become increasingly apparent over time (E10.5-11.5).…”
Section: Discussionmentioning
confidence: 99%